Bound to Impact: a best practices guide to term sheets in African Impact Investing deals - Pepper, Nicholas (Research of GSB, 2018)
This study focuses on the Impact Investing industry in sub-Saharan Africa through a comparative analysis of three industry-leading institutions' term sheets. A key output of this exploratory research is the development of a best practices guide to social and environmental covenants (clauses included in the term sheet). The researcher has compiled primary data through practitioner interviews; secondary data was compiled by analysing executed legal documents and templates. The process was conducted with academic rigour in order to categorise and compare specific information. Preliminary research involved the researcher exchanging with a DFI and two commercial Impact Investors. The DFI provides both equity and debt, whereas one of the commercial Investors specialises in private equity and the other in private debt. The institutions are industry agnostic. The study has the objective to test two linked null hypotheses:  Impact Investors do not align their terms sheets to their values; and  Impact Investors do not require that certain clauses be systematically included in order to protect their interests Through case studies, the research initially develops on the key elements of an equity term sheet and provides a fictitious debt term sheet as a reference. Equity and debt legal documents are compared and analysed independently. After having isolated and analysed social and environmental covenants, the researcher concludes that neither hypothesis can be rejected. Further research is recommended limiting the scope to a specific industry or a specific asset class. Understanding and comparing Development Finance Institutions' methods would be of value. A quantitative analysis would isolate the success factors and appropriate constraints on the legal documentation in order to maximise financial and social and environmental returns.